Manifesto on inhaled triple therapy in asthma: an Interasma (Global Asthma Association – GAA) document. (10th November 2022) - Braido, Fulvio; Tiotiu, Angelica; Guidos-Fogelbach, Guillermo; Baiardini, Ilaria; Cosini, Filippo; Correia de Sousa, Jaime; Bikov, Andras; Novakova, Sylvia; Labor, Marina; Kaidashev, Igor; Nedeva, Denislava; Kowal, Krzysztof; et al.
Abstract: Objective: The optimal use of drug combinations for the management of asthma is providing significant results. This has prompted Interasma (Global Asthma Association) to take a position on inhaled triple therapy in asthma.Methods: We performed an extensive literature research to clinical trials, meta-analyses, randomized controlled trials and systematic reviews.Results: Starting from an extensive literature review, Interasma executive committee discussed and approved this Manifesto, developed by Interasma scientific network (INES) members.Conclusions: The manifesto describes the evidence gathered to date and states, advocates, and proposes issues on inhaled corticosteroid (ICS) plus long-acting beta 2 agonist (LABA) and long-acting muscarinic antagonists (LAMA) with the aim of challenging assumptions, fostering commitment, and bringing about change.